جدلية استقطاب الاستثمار الأجنبي المباشر بين المنافع والتكاليف - ميدون, الياس (جامعة الوادي University of Eloued, 2020)
تسعى جل الدول والحكومات بإختلاف درجة تقدمها إلى استقطاب الاستثمار الأجنبي المباشر كآلية لتخصيص الموارد الاقتصادية العالمية النادرة، فضلا عن المزايا التي يجلبها هذا العنصر للاقتصاد الوطني. غير أن هذه المزايا قد تصاحبها آثار غير مرغوبة ولا محبذة خاصة في الأجل الطويل، وصارت هذه الآثار المترتبة عن الاستثمار الأجنبي المباشر موضوعا لجدل قوي بين المؤيدين والمعارضين له. وعليه حاولت الورقة البحثية بإستخدام التحليل النظري ومراجعة الادبيات، تبيان آثار هذا العنصر على كافة جوانب الاقتصاد المضيف من مزايا وسلبيات. وقد توصلت النتائج إلى: يمكن للاستثمار الأجنبي المباشر على المدى القصير والمتوسط المساهمة في تمويل وخدمة التنمية التنمية، وتصحيح الهيكل الاقتصادي فضلا عن تحسين وضعية ميزان المدفوعات. لكن قد ينجر عن استقطابه في المدى الطويل: عدم الاستقرار الاقتصادي بشويه الهيكل الاقتصادي ونزيف الموارد الاقتصادية فضلا عن الاضرار بالتنمية الاقتصادية. Most countries and governments with varying degrees of progress seek to attract foreign direct investment as a mechanism for allocating scarce global economic resources, as well as the advantages that this component brings to the national economy. However, these advantages may be accompanied by unwanted and desirable effects, especially in the long term, and these effects of FDI have become the subject of strong controversy between supporters and opponents of it. Accordingly, the research paper tried using theoretical analysis and reviewing the literature to show the effects of this element on all aspects of the host economy in terms of advantages and disadvantages. The results reached: FDI in the short and medium term can contribute to financing and development service development, correcting the economic structure as well as improving the balance of payments situation. But it may drag in its polarization in the long run: economic instability by distorting the economic structure and bleeding economic resources as well as damaging economic development.
The dialectic of attracting foreign direct investment between benefits and costs.
مقال
Keywords: الاستثمار الأجنبي المباشر ; النمو الاقتصادي ; التنمية الاقتصادية ; الاقتصاد الدولي